2021
DOI: 10.3390/cells10123495
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiles Reveal Downregulation of Low-Density Lipoprotein Particle Receptor Pathway Activity in Patients Surviving Severe COVID-19

Abstract: To assess the biology of the lethal endpoint in patients with SARS-CoV-2 infection, we compared the transcriptional response to the virus in patients who survived or died during severe COVID-19. We applied gene expression profiling to generate transcriptional signatures for peripheral blood mononuclear cells (PBMCs) from patients with SARS-CoV-2 infection at the time when they were placed in the Intensive Care Unit of the Pavlov First State Medical University of St. Petersburg (Russia). Three different bioinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
3
13
0
Order By: Relevance
“…On the other hand, the relevance of lipid metabolism for the pathogenesis of COVID-19 is stressed by many researchers [41][42][43]. The recently revealed downregulation of the lowdensity lipoprotein (LDL) metabolism in peripheral blood mononuclear cells of patients who survived severe COVID-19 [42] might be especially important, thus complementing our preliminary findings that have shown a correlation between the level of autoantibodies again oxidized LDL and 4-HNE protein adducts in the blood of COVID-19 patients who did not survive the disease [16]. This is not surprising because 4-HNE-modified epitopes dominate in the oxidized LDL [44].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the relevance of lipid metabolism for the pathogenesis of COVID-19 is stressed by many researchers [41][42][43]. The recently revealed downregulation of the lowdensity lipoprotein (LDL) metabolism in peripheral blood mononuclear cells of patients who survived severe COVID-19 [42] might be especially important, thus complementing our preliminary findings that have shown a correlation between the level of autoantibodies again oxidized LDL and 4-HNE protein adducts in the blood of COVID-19 patients who did not survive the disease [16]. This is not surprising because 4-HNE-modified epitopes dominate in the oxidized LDL [44].…”
Section: Discussionmentioning
confidence: 99%
“… [ 61 ] ITGAV 16 0.42241379 0.05534754 Expressed in downregulated level in surviving patients with COVID-19; Identified more vulnerable to invading lung cells than other cells of the respiratory tracts and nasopharynx. [ 62 , 63 ] TGFB3 15 0.37984496 0.04488816 Redirected to adopt Bacille CalmetteGuérin vaccination in a tuberculosis pathway enrichment test. [ 64 ] …”
Section: Resultsmentioning
confidence: 99%
“…Again, from the analysis of peripheral blood immune cells in COVID-19 patients [ 61 ], it was unearthed that the CD3G hub gene had a downregulated expression level in the cluster of blood immune cells known as CD 4 + and CD 8 +, both cells are also associated with COVID-19 patients with gastric cancer [ 47 ] and AD disease activities [ 50 ]. Following low-density lipoprotein particle receptor pathway activity in transcriptome study, ITGAV gene expression was found downregulated in COVID-19 patients [ 62 ]. ITGAV is integrins and integrins signals related gene; ITGAV was unpredictably expressed at a very high level in the lungs, signifying that it was more vulnerable to assaulting lung cells than other cells of the respiratory tracts and nasopharynx, according to an analysis of the transcriptome of COVID-19 patients with nasopharyngeal samples and other SARS-CoV-2 infections [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…VSIG4 may be involved in lung injury through induction of phagocytosis (22). VSIG4 activate macrophages, through induction of chemokines, promote the migration of inflammatory cells to the lesion area, and participate in the pathogenesis of arteriosclerosis STAB1 encodes an unusual type of multifunctional scavenger receptor that causes increased lipid uptake and transient lipid depletion in virus-infected areas and is associated with poor prognosis for COVID-19 (30). STAB1 expression may contribute to foam cell formation, monocyte adhesion/migration, and regulation of inflammation in atherosclerotic lesions (31).…”
Section: Discussionmentioning
confidence: 99%
“…STAB1 encodes an unusual type of multifunctional scavenger receptor that causes increased lipid uptake and transient lipid depletion in virus-infected areas and is associated with poor prognosis for COVID-19 ( 30 ). STAB1 expression may contribute to foam cell formation, monocyte adhesion/migration, and regulation of inflammation in atherosclerotic lesions ( 31 ).…”
Section: Discussionmentioning
confidence: 99%